Checkpoint Inhibitor Myocarditis–Mediated Conduction Abnormalities Reversed With Early Intravenous Steroid Administration: A Case Report - Andrew S. Baird; Jeremy R. Burt; Stavros G. Drakos; Christopher A. Groh; Libo Wang (Annals of Internal Medicine: Clinical Cases)
A man receiving nivolumab and ipilimumab presented to urgent care following a syncopal episode with troponin elevation before rapidly developing progressive conduction abnormalities from checkpoint inhibitor–mediated myocarditis, which initially required pacing. His arrhythmia resolved with a prompt regimen of steroids. There is a paucity of literature supporting treatment strategies for heart block related to immune checkpoint inhibitor–mediated myocarditis. Most cases have not been treated promptly with aggressive steroid therapy, and rarely have patients been liberated from pacemaker dependence following treatment. This case demonstrates the potentially devastating adverse effects of checkpoint inhibition and emphasizes the necessity of timely diagnosis and treatment.